136 Sleep and Porphyromonas gingivalis K-Capsular IgG Serotypes: A Study in the Old Order Amish. (3rd May 2021) - Spector, Anna; Wadhawan, Abhishek; Constantine, Niel; Ryan, Kathy; Mohyuddin, Iqra; Dagdag, Aline; Brenner, Lisa; Daue, Melanie; Schifferle, Robert; Ernst, Robert; Mitchell, Braxton; Reynolds, Mark; et al.
Abstract: Introduction: Sleep problems and periodontal disease have a bidirectional relationship and are independently linked with depression, dementia, and metabolic disease. Inadequate sleep can worsen inflammation, a hallmark of periodontal disease, and the activation of the immune system can alter sleep/wake cycles. A key player in periodontal disease is Porphyromonas gingivalis, a bacteria that can translocate to the brain and induce miRNA's. Antibodies to P. gingivalis capsular virulence factors, K1-7, have been used to estimate P. gingivalis virulence. This study was conducted to explore cross-sectional associations between seropositivity of K serotypes of P. gingivalis and measures of self-reported impairment in sleep. If identified, these links would provide a rationale to initiate causality and mediation studies. We hypothesized that sleep impairment is positively associated with P. gingivalis K IgG serointensity. Methods: 880 Old Order Amish aged 44.8 (SD: 17.2 years); 360 men (40.91%), 520 women (59.09%) responded to an adapted Pittsburgh-Sleep-Quality-Index questionnaire. IgG serointensity to 7 K-capsular P. gingivalis serotypes were measured with ELISAs. We tested for the association of log-transformed serotype IgG intensity and positivity (successively defined as within the top 5% and 25% for each serotype) with sleep parameters (as binary and continuous variables) using linear and logistic regressions, adjusting for age and sex. Results: We confirmed no hypothesized associations between any of the sleep problems on the PSQI and K serotype serointensity and seropositivity. Exploratory analysis returned a negative association of log-transformed K3 IgG with daytime sleepiness (p=0.01); however, this did not resist adjustment for multiple comparisons and was inconsistent with the direction of the hypothesis. Conclusion: Strengths of the study include the reduced smoking prevalence in the Amish and the relatively homogenous lifestyle, reducing confounding. The results imply P. gingivalis serotypes are not associated with sleep disturbance. Limitations are self-reporting of sleep, cross-sectional approach and limited generalizability. Results do not support an association between P. gingivalis K serotypes and sleep-problems. Support (if any): MVM-CoRE